(untitled) (The Review of Diabetic Studies, 2025)
The continuous circulation and contact of currency notes with contaminants heightens the risk of transmitting many diseases to humans. A study was done to enhance public awareness and assess the magnitude of fungal contamination in Indian rupees collected from 10 distinct sources. A total of seven Indian currency notes with denominations of 10, 20, 50, 100, 200, 500, and 2000 ₹ were obtained from different sources including a butcher, college student, street food shop, general store, fruit shop, conductor, clinic, bank, medical shop, and school in a random manner. The fungi were isolated and identified using the cotton swab technique and Czapek’s agar, resulting in the detection of 11 fungal species. Aspergillus exhibited the highest prevalence, accounting for 30% of the occurrences, whereas Penicillium followed with a prevalence of 15%. The occurrence of Fusarium and Chaetomium was observed at a frequency of 10%. The investigation reveals that Mucor, Syncephalastrum racemosum, cunninghamella, Curvularia, Rhizopus arrhizus, Cladosporium variabile, and Periconia hispudila collectively account for a mere 5% of the overall microbial load detected on bank notes.The prevailing organisms identified were Aspergillus sp and Penicillium sp. The ₹ 10 and ₹ 20 notes, received from various sources including college students, butchers, street food shops, general stores, and fruit shops, had the most significant fungal presence. Conversely, the bills had the lowest amount of microorganisms. Nevertheless, lower value notes exhibit a greater microbial burden as a result of their frequent circulation. Consequently, it is crucial to handle paper notes appropriately and embrace hygienic measures to prevent the transmission of infections.